Rethinking metabotropic glutamate receptor 5 pathological findings in psychiatric disorders: implications for the future of novel therapeutics - Newell, Kelly A (BioMed Central, 2014)
BACKGROUND: Pharmacological modulation of metabotropic glutamate receptor 5 (mGluR5) is of marked interest as a novel therapeutic mechanism to treat schizophrenia and major depression. However, the status of mGluR5 in the pathophysiology of these disorders remains unknown. DISCUSSION: The majority of studies in the schizophrenia post-mortem brain indicate that total mGluR5 expression is unaltered. However, close examination of the literature suggests that these findings are superficial, and in actuality, a number of critical factors have not yet been considered; alterations may be highly dependent on brain region, neuronal population or molecular organisation in specific cellular compartments. A number of genetic knockout studies (mGluR5, Norbin, Homer1 etc.) continue to lend support to a role of mGluR5 in the pathology of schizophrenia, providing impetus to explore the regulation of mGluR5 beyond total mGluR5 protein and mRNA levels. With regards to major depression, preliminary evidence to date shows a reduction in total mGluR5 protein and mRNA levels; however, as in schizophrenia, there are no studies examining mGluR5 function or regulation in the pathological state. A comprehensive understanding of mGluR5 regulation in major depression, particularly in comparison to schizophrenia, is crucial as this has extensive implications for mGluR5 targeting novel therapeutics, especially considering that opposing modulation of mGluR5 is of therapeutic interest for these two disorders. SUMMARY: Despite the complexities, examinations of post-mortem human brain provide valuable insights into the pathologies of these inherently human disorders. It is important, especially with regards to the identification of novel therapeutic drug targets, to have an in depth understanding of the pathophysiologies of these disorders. We posit that brain region- and cell type-specific alterations exist in mGluR5 in schizophrenia and depression, with evidence pointing towards altered regulation of this receptor in psychiatric pathology. We consider the implications of these alterations, as well as the distinction between schizophrenia and depression, in the context of novel mGluR5 based therapeutics.